The solution of -2/3X + 4/3 = -10/3 by first eliminating all fractions is 7.0006
<u>Solution:</u>
We have been given an equation as follows:
![-\frac{2}{3 x}+\frac{4}{3}=-\frac{10}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%20x%7D%2B%5Cfrac%7B4%7D%7B3%7D%3D-%5Cfrac%7B10%7D%7B3%7D)
And we have been asked to solve each equation by first eliminating all fractions.
The only way to solve this equation is by converting each of its components into decimals since it is stated in the question that we should not solve it in fraction form.
To do so we will individually convert the fractions to decimals and then substitute them back into the equation.
The 1st fraction in decimal form is:
![-\frac{2}{3}=-0.6666](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7D%3D-0.6666)
The 2nd fraction in decimal form is:
![\frac{4}{3}=1.3333](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D%3D1.3333)
And the 3rd fraction in decimal form is:
![-\frac{10}{3}=-3.3333](https://tex.z-dn.net/?f=-%5Cfrac%7B10%7D%7B3%7D%3D-3.3333)
So, now we substitute the decimals instead of the fractions in the given equation as follows:
![\begin{array}{l}{-0.6666 x+1.3333=-3.3333} \\\\ {-0.6666 x=-3.3333-1.3333} \\\\ {x=-\frac{4.6666}{-0.6666}} \\\\ {x=7.0006}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bl%7D%7B-0.6666%20x%2B1.3333%3D-3.3333%7D%20%5C%5C%5C%5C%20%7B-0.6666%20x%3D-3.3333-1.3333%7D%20%5C%5C%5C%5C%20%7Bx%3D-%5Cfrac%7B4.6666%7D%7B-0.6666%7D%7D%20%5C%5C%5C%5C%20%7Bx%3D7.0006%7D%5Cend%7Barray%7D)
Therefore, the value of x in decimal from is 7.0006